2022
DOI: 10.36987/jpbn.v8i2.2642
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Biology Pleco (Pterygoplichthys pardalis Castelnau 1855) in Ciliwung River

Abstract: Pterygoplichthys pardalis is a type of fish that is widely used by people around the Ciliwung River as raw material for food production. In addition, P. pardalis has not been cultivated. The process of fish farming requires a number of information and data on fish such as reproductive biology. Therefore, the research aimed is calculating the reproductive aspects of P. pardalis. The result for this research can be applied for fish farmers to start P. pardalis bredding process. The methods used are P. pardalis s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Other studies have reported lengths of up to 40cm (Geerinckx et al, 2007). Moreover, some investigations reported lengths of up to 70 cm (Kottelat & Whitten, 1996;Nelson et al, 2016;Elfidasari et al, 2022). The differences in the length-frequency distribution of P. pardalis mentioned above are influenced by their habitats.…”
Section: Discussionmentioning
confidence: 92%
“…Other studies have reported lengths of up to 40cm (Geerinckx et al, 2007). Moreover, some investigations reported lengths of up to 70 cm (Kottelat & Whitten, 1996;Nelson et al, 2016;Elfidasari et al, 2022). The differences in the length-frequency distribution of P. pardalis mentioned above are influenced by their habitats.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, the peak spawning of O. matanensis fish occurs from August to September (Eragradhini, 2020). Additionally, the peak spawning of Pleco fish, Pterygoplichthys pardalis in the Ciliwung River is in February and May (Elfidasari et al, 2022).…”
Section: ____________________________________________________________...mentioning
confidence: 99%